The impact of development project’s funds to poverty reduction in Tanzania : A case study of DASIP in Ukerewe district - Salvatory, Frank .M. (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance of Mzumbe University